Cell nucleus activity during post-embryonic development of Apis melliferaL. (Hymenoptera: Apidae). Intranuclear acid phosphatase - Landim, Carminda Da Cruz [UNESP]; Reginato, Rejane Daniele [UNESP]; De Moraes, Regina Lucia Morelli Silva [UNESP]; Cavalcante, Vagner Melo [UNESP] (My University, 2002)
We report nuclear acid phosphatase activity in the somatic (intra-ovariolar and stromatic) and germ cells of differentiating honey bee worker ovaries, as well as in the midgut cells of metamorphosing bees. There was heterogeneity in the intensity and distribution of electron dense deposits of lead phosphate, indicative of acid phosphatase activity in the nuclei of these tissues, during different phases of post-embryonic bee development. This heterogeneity was interpreted as a variation of the nuclear functional state, related to the cell functions in these tissues.
Keywords: Apis mellifera; Honey bee; Intranuclear acid phosphatase activity; Post-embryonic development; acid phosphatase; lead phosphate; phosphate; unclassified drug; animal cell; animal tissue; cell activity; cell cycle phase; cell function; cell heterogeneity; cell nucleus; embryo; embryo development; enzyme activity; germ cell; honeybee; metamorphosis; midgut; nonhuman; ovary; animal; bee; digestive system; electron microscopy; enzymology; female; insect; larva; metabolism; ultrastructure; Animalia; Apidae; Apis; Apoidea; Hymenoptera; Acid Phosphatase; Animals; Bees; Cell Nucleus; Digestive System; Female; Larva; Microscopy, Electron; Ovary; Pupa